Maltreatment, homicide and access to specialised palliative care among children and young adults with a life-limiting condition: a nationwide population-based study - Hsin-Yi Chang; Shih-Chun Lin; Mei-Chih Huang (BMJ Paediatrics Open)
Objective This study compared the differences in the rates of maltreatment and homicide deaths between children and young adults with and without a life-limiting condition (LLC) and determined whether this affects the likelihood of receiving specialised palliative care (SPC) services before death.Design A nationwide retrospective observational study.Setting Taiwan.Patients Children and young adults aged 0–25 years with LLCs and maltreatment were identified within the Health and Welfare Data Science Centre by International Classification of Diseases codes. Deaths were included within the Multiple Causes of Death Data if they occurred between 2016 and 2017.Main outcome measures Rates of maltreatment, homicide deaths and SPC referrals.Results Children and young adults with underlying LLCs experienced a similar rate of maltreatment (2.2 per 10 000 vs 3.1 per 10 000) and had a 68% decrease in the odds of homicide death (19.7% vs 80.3%, OR, 0.32; 95% CI 0.18 to 0.56) than those without such conditions. Among those with LLCs who experienced maltreatment, 14.3% (2 out of 14) had received SPC at least 3 days before death. There was no significant difference in SPC referrals between those who experienced maltreatment and those who did not.Conclusions The likelihood of being referred to SPC was low with no significant statistical differences observed between children and young adults with maltreatment and without. These findings suggest a need for integrating SPC and child protection services to ensure human rights are upheld.